A stylistic analysis of the use of modality to identify the point of view in a short story: - Jose, Cristina M. Parina; Dasha de Leon, Kristine (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
The present paper used the modal framework of Simpson in doing a stylistic analysis of the story “Things You Don’t Know” by Ian Rosales, a highly-acclaimed Filipino writer. Since stylistics has always been concerned with how readers interpret the texts by focusing on linguistic choices, the modal choices of the writer based on Simpson’s modal framework would allow the readers to identify the attitude of the narrator. Indeed, results show that the epistemic type of modal was preponderant –this type apparently allows the readers to feel the narrator’s uncertainty in situations or events. In addition, this modal framework also enables the readers to further identify the shade of a text, since the choice of modals highlights either a positive, negative, or neutral shade of a story. Since the epistemic modal was the most pronounced, the story is definitely negative in shade, and this can be inferred in the short story where the narrator is uncertain what was going on in her everyday affairs. In turn, this uncertainty is emphasised by the narrator’s dependence on his/her perception of external appearances or surroundings.